Kinetic analysis and test-retest variability of the radioligand [11C](R)-PK11195 binding to TSPO in the human brain - a PET study in control subjects - Jučaite, Aurelija; Cselényi, Zsolt; Arvidsson, Annie; Åhlberg, Gabrielle; Julin, Per; Varnäs, Katarina; Stenkrona, Per; Andersson, Jan; Halldin, Christer; Farde, Lars (EJNMMI research, 2012)
Background Positron-emission tomography and the radioligand [ 11 C](R)-PK11195 have been used for the imaging of the translocator protein (TSPO) and applied to map microglia cells in the brain in neuropsychiatric disorders. [ 11 C](R)-PK11195 binding has been quantified using reference region approaches, with the reference defined anatomically or using unsupervised or supervised clustering algorithms. Kinetic compartment modelling so far has not been presented. In the present test-retest study, we examine the characteristics of [ 11 C](R)-PK11195 binding in detail, using the classical compartment analysis with a metabolite-corrected arterial input function. Methods [ 11 C](R)-PK11195 binding was examined in six control subjects at two separate occasions, 6 weeks apart. Results of one-tissue and two-tissue compartment models (1TCM, 2TCM) were compared using the Akaike criteria and F -statistics. The reproducibility of binding potential ( BP ND ) estimates was evaluated by difference in measurements (error in percent) and intraclass correlation coefficients (ICCs). Results [ 11 C](R)-PK11195 binding could be described by 2TCM which was the preferred model. Measurement error (in percent) indicated good reproducibility in large brain regions (mean error: whole brain 4%, grey matter 5%), but not in smaller subcortical regions (putamen 25%, caudate 55%). The ICC values were moderate to low, highest for the white matter (0.73), whole brain and thalamus (0.57), and cortical grey matter (0.47). Sizeable [ 11 C](R)-PK11195 BP ND could be identified throughout the human brain (range 1.11 to 2.21). Conclusions High intra-subject variability of [ 11 C](R)-PK11195 binding limits longitudinal monitoring of TSPO changes. The interpretation of [ 11 C](R)-PK11195 binding by 2TCM suggests that the presence of specific binding to TSPO cannot be excluded at physiological conditions.